Regulation of Dendritic Spine Morphology in Hippocampal Neurons by Copine-6. (3rd February 2017) - Burk, Katja; Ramachandran, Binu; Ahmed, Saheeb; Hurtado-Zavala, Joaquin I; Awasthi, Ankit; Benito, Eva; Faram, Ruth; Ahmad, Hamid; Swaminathan, Aarti; McIlhinney, Jeffrey; Fischer, Andre; Perestenko, Pavel; et al.
Abstract: Dendritic spines compartmentalize information in the brain, and their morphological characteristics are thought to underly synaptic plasticity. Here we identify copine-6 as a novel modulator of dendritic spine morphology. We found that brain-derived neurotrophic factor (BDNF) – a molecule essential for long-term potentiation of synaptic strength – upregulated and recruited copine-6 to dendritic spines in hippocampal neurons. Overexpression of copine-6 increased mushroom spine number and decreased filopodia number, while copine-6 knockdown had the opposite effect and dramatically increased the number of filopodia, which lacked PSD95. Functionally, manipulation of post-synaptic copine-6 levels affected miniature excitatory post-synaptic current (mEPSC) kinetics and evoked synaptic vesicle recycling in contacting boutons, and post-synaptic knockdown of copine-6 reduced hippocampal LTP and increased LTD. Mechanistically, copine-6 promotes BDNF-TrkB signaling and recycling of activated TrkB receptors back to the plasma membrane surface, and is necessary for BDNF-induced increases in mushroom spines in hippocampal neurons. Thus copine-6 regulates BDNF-dependent changes in dendritic spine morphology to promote synaptic plasticity.